Finnish information society and its regionalisation in Western Finland and Lapland 1994-2004 - Ingerö, Oula (2009)
Only abstract. Paper copies of master’s theses are listed in the Helka database (http://www.helsinki.fi/helka). Electronic copies of master’s theses are either available as open access or only on thesis terminals in the Helsinki University Library. Vain tiivistelmä. Sidottujen gradujen saatavuuden voit tarkistaa Helka-tietokannasta (http://www.helsinki.fi/helka). Digitaaliset gradut voivat olla luettavissa avoimesti verkossa tai rajoitetusti kirjaston opinnäytekioskeilla. Endast sammandrag. Inbundna avhandlingar kan sökas i Helka-databasen (http://www.helsinki.fi/helka). Elektroniska kopior av avhandlingar finns antingen öppet på nätet eller endast tillgängliga i bibliotekets avhandlingsterminaler. This study evaluates regional information society strategies and their implementation in Western Finland and Lapland in the years 1994-2004. It reviews how these provinces have tried to utilise information and communication technologies (ICTs) in order to create welfare services that are jeopardised by threats such as globalisation and migration. Finland has recently been among the most developed countries when it comes to the information society. Provinces such as Western Finland and especially Lapland aren't, however, generally seen as being as developed as some other areas in Finland. Furthermore, many areas in these provinces suffer from trends that affect their possibilities to create welfare and ICT services. By utilising three analysis dimensions (networks, regional advantages, accessibility and user skills) it is found that these provinces" information society strategies differ from each other and that these strategies take into consideration both national goals as well as local settings. As a conclusion is drawn that that the information society development is taking quite well place in both provinces. Networks such as the Centres of Expertise and Multipolis have balanced regional development in both provinces. There have also been several projects that have increased accessibility and user skills in ...